2020
DOI: 10.3390/cancers12030664
|View full text |Cite
|
Sign up to set email alerts
|

Microcellular Environmental Regulation of Silver Nanoparticles in Cancer Therapy: A Critical Review

Abstract: Silver nanoparticles (AgNPs) play significant roles in various cancer cells such as functional heterogeneity, microenvironmental differences, and reversible changes in cell properties (e.g., chemotherapy). There is a lack of targets for processes involved in tumor cellular heterogeneity, such as metabolic clampdown, cytotoxicity, and genotoxicity, which hinders microenvironmental biology. Proteogenomics and chemical metabolomics are important tools that can be used to study proteins/genes and metabolites in ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(37 citation statements)
references
References 148 publications
(190 reference statements)
0
32
0
Order By: Relevance
“…The present results suggested that reduced IL-1β could be associated with the impairment of the innate immune response caused by AgNPs. Previous studies have stated that AgNPs can activate various pathways, including the MAPK and NF-κB pathways, leading to the transcription of many genes involved in inflammatory responses and triggering harmful inflammatory responses [ 37 ]. However, a low dose of AgNPs slightly upregulated the expression of NF-κB and IL-1β , and these levels were downregulated with increasing doses.…”
Section: Discussionmentioning
confidence: 99%
“…The present results suggested that reduced IL-1β could be associated with the impairment of the innate immune response caused by AgNPs. Previous studies have stated that AgNPs can activate various pathways, including the MAPK and NF-κB pathways, leading to the transcription of many genes involved in inflammatory responses and triggering harmful inflammatory responses [ 37 ]. However, a low dose of AgNPs slightly upregulated the expression of NF-κB and IL-1β , and these levels were downregulated with increasing doses.…”
Section: Discussionmentioning
confidence: 99%
“…Covalent modifications are mainly based on direct chemical bonds and linker molecules. AgNPs can be coated with peptides, like for example CSG-LL37 peptide [63], antibodies, such as immunoglobulin G [64], polymers, like polyvinyl alcohol (PVA), polyethylene glycol (PEG) and polyvinylpyrrolidone (PVP) [65], nucleic acids, such as DNA [66], and tumor markers [67] (Figure 2), thus increasing the effectiveness of target-directed drug release, and allowing its use in other applications, like in imaging techniques and target treatments with anticancer drugs, for example doxorubicin [5,68,69]. The state of the art of anticancer drugs coupled to AgNPs is discussed in following.…”
Section: Surface Modificationsmentioning
confidence: 99%
“…The benefit of nanoparticles is the broad types of materials used together with a range of different functionalizations [ 18 ]. Their putative application for medical purposes has been recently summarized [ 19 , 20 , 21 ]. We here combined gas plasma treatment with nanoparticle exposure in three melanoma cell lines and found combined cytotoxicity in five out of seven nanoparticle types investigated.…”
Section: Introductionmentioning
confidence: 99%